HUBUNGAN ANTARA TINGKAT PENDIDIKAN IBU DAN KECERDASAN LOGIKA-MATEMATIKA SISWA R.A. MUSLIMAT N.U. PONOROGO - Hidayati, Kurnia (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: This study describes the relationship between motherâs education level and studentsâ logic-mathematical intelligence at the RA NU 074 Ronowijayan Ponorogo. This study was conducted with a quantitative approach through the study of documentation and questionnaires. The data is processed by the formula percentages and standard deviations and analyzed by correlation of contingency coefficients. The results showed that (1) The level of maternal education were high for as many as 10 people or 50%, the categories are as many as 7 people or 35% and the low category as many as 3 people or 15%; (2) Logical-mathematical intelligence which include high category with a score of> 62.103 as many as three people, the medium category with a score of 44.697 to 62.103 as many as 13 people and low category with a score of <44.697 of 4 people and (3) There is a positive and significant relationship between motherâs education level and logic-mathematical intelligence RA NUâs 074 students Ronowijayan Ponorogo at a significance level of 5% with Î¦0> table or 0.6000606> 0.444 then H0 is rejected and Ha accepted.ÙØ§ÙØ·ÙØ£Ø§ Ø©Ø¶ÙØ± Ø¨ÙØ§Ø·Ù ÙØ¶Ø§ÙØ±ÙØ§ ÙÙØ·ÙÙÙØ§ Ø¡Ø§ÙØ°ÙØ§Ø¨ ØªØ§ÙÙÙØ£Ø§ ÙØ¯Ù ÙÙØ¨ØªØ±ÙØ§ ÙÙØªØ³ÙÙØ§ ÙÙØ¨ Ø©ÙÙØ§Ø¹ÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ØªÙÙ ÙØ¨Â Ø©Ø³Ø§Ø±Ø¯ ÙÙØ±Ø· ÙØ¹ ÙÙ ÙÙÙØ§ ÙØ®Ø¯ÙÙØ§Ø¨ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ØªÙØ±Ø¬Ø£ .ÙØºÙØ±ÙÙÙÙ ÙØ§ÙØ§ÙØ¬ÙÙÙÙØ± 074 Ø¡Ø§ÙÙØ¹ÙØ§ Ø©Ø¶ÙÙ " ØªØ§ÙÙØ³ÙÙØ§ "Â ÙØ¹ ÙÙ ÙØªØÙ ÙÙØ§Ø±ÙØÙØ§Ø§ Ø±Ø§ÙØ¹ÙÙØ§Ù Ø©ÙÙØ¦ÙÙØ§ Ø©Ø¨Ø³ÙÙØ§ Ø©ØºÙØµ ÙÙØ±Ø· ÙØ¹ ØªØ§ÙØ§ÙØ¨ÙØ§ ÙÙØ§Ø¹ØªÙ .ØªØ§ÙØ§ÙØ¨ØªØ³ÙØ§Ø§Ù Ø©Ø¨ÙØªÙÙÙØ§ ÙØ¦Ø§Ø«ÙÙØ§Â ØªØ§ÙÙÙØ£Ø§ ÙØ¯Ù ÙÙØ¨ØªØ±ÙØ§ ÙÙØªØ³ÙÙØ§ )1( : ÙÙØ¹ Ø«ØØ¨ÙØ§ Ø¬Ø¦Ø§ØªÙ ØªÙ ÙØ¯. Korelasi Koefisien KontingensiÂ  ÙÙØ±Ø·Â ( Ø©ÙÙØ§Ø³ÙØ§ Ø©ÙØ¨Ø·ÙØ§ ÙÙÙ Ø) 35 ÙØ£ ØªØ§ÙÙØ£ 7 ( Ø©Ø·Ø³ÙØªÙÙØ§ Ø©ÙØ¨Ø·ÙØ§ ÙÙÙ Ø ) 50% ÙØ£ ØªØ§ÙÙØ£ 10 ( Ø©ÙÙØ§Ø¹ÙØ§ Ø©ÙØ¨Ø·ÙØ§ ÙÙÂ ÙÙÙ ØØ¨ÙØ§Ø· 3<62Ø103 Ø©Ø¬ÙØªÙÙØ§Ø¨ Ø©ÙÙØ§Ø¹ÙØ§ Ø©ÙØ¨Ø·ÙØ§ ÙÙ ÙØ¶Ø§ÙØ±ÙØ§ ÙÙØ·ÙÙÙØ§ Ø¡Ø§ÙØ°ÙØ§Ù )2( . ) 15% ÙØ£ ØªØ§ÙÙØ£ 3Â ÙÙØ¨ØªØ±ÙØ§ ÙÙØªØ³ÙÙØ§ ÙÙØ¨ ÙÙØ¹Ù ÙØ° Ø©ÙÙØ§Ø¹ÙØ§ Ø¯Ø¬ÙØª )3( . Ø¨ÙØ§Ø· 4 Ø¯Ø¯Ø¹ÙØ§Â  > 44Ø697 Ø©Ø¬ÙØªÙÙØ§Ø¨ Ø©Ø·Ø³ÙØªÙÙØ§ Ø©ÙØ¨Ø·ÙØ§Â 074 Ø¡Ø§ÙÙØ¹ÙØ§ Ø©Ø¶ÙÙ Â« ØªØ§ÙÙØ³ÙÙØ§ Â« ÙØ§ÙØ·ÙØ£Ø§ Ø©Ø¶ÙØ± ÙÙ Ø¨ÙØ§Ø·ÙØ§ ÙØ¯Ù ÙØ¶Ø§ÙØ±ÙØ§ ÙÙØ·ÙÙÙØ§ Ø¡Ø§ÙØ°ÙØ§ ÙÙØ¨Ù ØªØ§ÙÙÙØ£Ø§ ÙØ¯ÙÂ .Â Â  ÙÙØ¹Ù ÙØ° ÙÙØªØ³ÙÙØ§ ÙÙ ÙØºÙØ±ÙÙÙÙ ÙØ§ÙØ§ÙØ¬ÙÙÙÙØ±.ÙØ§ÙØ¨ÙÙ ( Ha ) ÙØ±Ø§ÙØªØ®ÙØ§Ø§ Ø¶Ø±ÙÙØ§Ù Ø§Ø¯ÙØ¯Ø±Ù ( H0) ÙØºÙØ§ÙØ§ Ø¶Ø±ÙÙØ§ ÙØ§Ù Ø§Ø°ÙØ¨